Factors Affecting Customer Loyalty: A Case of Kunming Mingzhu Environmental Protection Technology Co, Ltd - Hu, Rong; Tantasanee, Somchai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This study employs mixed-method research aiming to study the factors affecting customer loyalty of Kunming Mingzhu Environmental Protection Technology Co., Ltd. The research location is Kunming Mingzhu Environmental Protection Technology Co., Ltd. in Yunnan, China. The population is 100 and the sample size is 80. The research instruments include the questionnaire for the quantitative research method and the interview for the qualitative method. The data analysis treatment comprises of multiple linear regression for quantitative analysis and content analysis was used for qualitative analysis. The results show that service quality, product quality, brand image and brand awareness have a significant impact on customer satisfaction, and customer satisfaction has a significant impact on customer loyalty. Therefore, the enterprise must pay attention to these factors and strengthen their own service quality, product quality, brand image and brand awareness to improve customer satisfaction and customer loyalty.